Modos de conhecimento: por uma filosofia rizomática da arte - Pedro de Freitas Veneroso (2023)
This dissertation reflects on the ontology and epistemology of art, diferentiating the approaches to art as a field – territorial perspective –; as a system; based on an ecosystems logic – rhizomatic –; and as a mode of knowledge. Based on the recognition that indeterminacy and uncertainty are essential aspects related to the development of knowledge and the processes of signification and communication, we put forward a discussion focused on the philosophy of art, a field which, since the 20th century, is notorious for having borders that are dificult to define. Throughout this investigation, art goes from being a noun that categorizes objects to being a state and a mode of knowledge through which – together with science and philosophy – we can analyze and produce objects, actions and events in the world: the artistic, scientific and philosophical modes of knowledge. In this sense, an object or a situation will not be understood and artistic by definition – an ontological approach related to the understanding of art as a field –, but only examined momentarily as art when it is related to a rhizome shared with the world and with other objects and situations that are recognized as being artistic. With that we do not intend to substitute the essentialist theories of art that operate in this system in a reductive capacity, but to provide a theory that can encompass larger and relational analytical scales based on the understanding of art as a mode of knowledge, a rhizomatic logic that relates to and continues several philosophical endeavors of the 20th century, among which systems theory, complexity and the rhizome as conceptualized by Gilles Deleuze and Félix Guattari.